INCREASE OF WAVE HEIGHT DUE TO TRANSITION IN WIND DIRECTION – EXAMPLE: RIJEKA BAY (Advances in Civil and Architectural Engineering, 2021)
Surface wind wave dynamics were analyzed during wind transition from the third to the fourth quadrant, with the transition from Sirocco to Libeccio used as an example. This research is focused on the deep-water area in front of the Rijeka port. The analyses utilized a numerical model for wave generation, covering the entire Adriatic basin. Numerical simulations were conducted for relevant situations during the period 1998-2001. The numerical model was forced by the wind field obtained from the Aladin-HR atmospheric model. Numerical simulations were conducted in two steps, initially using hypothetical scenarios with homogenous and stationary wind fields, followed by simulations based on nonstationary wind fields from the Aladin-HR atmospheric model. The first step was used to confirm the hypothesis that significant wave heights rise during the transition of wind direction in the analyzed area. Model simulations in step two verified the assumption that the observed phenomenon can also occur in real atmospheric conditions. The results of the model simulations indicate the onset of a significant wave height increase during the transition of wind direction from the SSE to SW in a wider area that includes Kvarner and Rijeka bay. The increase in wind velocity results in a more noticeable significant wave height maximum.